Climatology and Evolution of the Antarctic Peninsula Föhn Wind‐Induced Melt Regime From 1979–2018. Issue 4 (10th February 2021) - Laffin, M. K.; Zender, C. S.; Singh, S.; Van Wessem, J. M.; Smeets, C. J. P. P.; Reijmer, C. H.
Abstract: Warm and dry föhn winds on the Antarctic Peninsula (AP) cause surface melt that can destabilize vulnerable ice shelves. Topographic funneling of these downslope winds through mountain passes and canyons can produce localized wind‐induced melt that is difficult to quantify without direct measurements. Our Föhn Detection Algorithm (FöhnDA) identifies the surface föhn signature that causes melt from measurement by 12 Automatic Weather Stations on the AP, that train a machine learning model to detect föhn in 5 km Regional Atmospheric Climate Model 2 (RACMO2.3p2) simulations and in the ERA5 reanalysis model. We estimate the fraction of AP surface melt attributed to föhn and possibly katabatic winds and identify the drivers of melt, temporal variability, and long‐term trends and evolution from 1979–2018. We find that föhn wind‐induced melt accounts for 3.1% of the total melt on the AP and can be as high at 18% close to the mountains where the winds funnel through mountain canyons. Föhn‐induced surface melt does not significantly increase from 1979–2018, despite a warmer atmosphere and more positive Southern Annular Mode. However, a significant increase (+0.1 Gt y‐1) and subsequent decrease/stabilization occur in 1979–1998 and 1999–2018, consistent with the AP warming and cooling trends during the same time periods. Föhn occurrence, more than föhn strength, drives the annual variability in föhn‐induced melt. Long‐term föhn‐induced melt trends and evolution are attributable to seasonal changes in föhn occurrence, with increased occurrence in summer, and decreased occurrence in fall, winter, and early spring over the past 20 years. Plain Language Summary: Surface melt on the glaciers and floating ice shelves of the Antarctic Peninsula can contribute to sea‐level rise via run‐off to the ocean and by ice‐shelf destabilization and reduced buttressing against glacier flow to the ocean. Surface melt on the Antarctic Peninsula has traditionally been attributed to sunlight melting snow although more recent studies demonstrate significant contributions in all seasons from warm, downslope winds called föhn winds. It is important to understand where these winds cause melt, when they cause melt, how much melt, and are they changing through time? We use weather stations on the Antarctic Peninsula, model data, and Machine‐Learning techniques to characterize these warm winds. We find they occur in every season, including winter when there is no sunlight to melt the snow surface. Föhn wind‐induced melt accounts for 3.1% of the total melt on the Antarctic Peninsula and can be as high as 18% close to the mountains where the winds funnel through mountain canyons. Overall there has not been a significant increase in melt caused by föhn winds in the past 40 years, although the seasonality of the winds and associated melt are changing. Key Points: We use machine learning, trained with surface observations to identify föhn winds on the Antarctic Peninsula and their impact on melt Föhn‐induced melt trends mirror surface temperature trends with increased melt from 1979 to 1998 and stable/decreased melt from 1999 to 2018 Föhn occurrence, or the number of hours föhn melt occurs, drives annual föhn‐induced melt variability and evolution